Magical Circles in Pandemic Times: On Narrative Roleplaying Games at the Tobar García Children’s Hospital for Mental Health (Buenos Aires, 2020–21) - Barugel, Santiago; La Haije, Marileen (Journal of Childhood Studies, 2024)
This article focuses on a narrative roleplaying game collectively constructed and performed at the Dr. C. Tobar García Children’s Hospital for Mental Health in Buenos Aires, Argentina, during the COVID-19 pandemic. During this game, the hospitalized children, many of whom faced situations of extreme social vulnerability, learned concrete narrative skills (e.g., developing a fictional character, narrative plotting) which they could later use for playful practices of collaborative storytelling in their homes, schools, and neighbourhoods. We consider that it is necessary to study and share this creative process with the hope to enhance playful practices of collaborative storytelling with children in vulnerable contexts.